2015
DOI: 10.4329/wjr.v7.i9.266
|View full text |Cite
|
Sign up to set email alerts
|

Radiation signature on exposed cells: Relevance in dose estimation

Abstract: The radiation is considered as a double edged sword, as its beneficial and detrimental effects have been demonstrated. The potential benefits are being exploited to its maximum by adopting safe handling of radionuclide stipulated by the regulatory agencies. While the occupational workers are monitored by personnel monitoring devices, for general publics, it is not a regular practice. However, it can be achieved by using biomarkers with a potential for the radiation triage and medical management. An ideal bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…A higher dose rate means a lower chance for DNA repair. 19 When compared to cytogenetic dose-response curves using x-ray irradiation, the coefficients developed by this study's curves are similar to published data ( Table 5). The calibration curve aims to determine an accurate dose from a set of analyzed cells and dicentric frequencies, ideally within 20% of the actual whole-body dose received by the individual.…”
Section: Discussionsupporting
confidence: 82%
“…A higher dose rate means a lower chance for DNA repair. 19 When compared to cytogenetic dose-response curves using x-ray irradiation, the coefficients developed by this study's curves are similar to published data ( Table 5). The calibration curve aims to determine an accurate dose from a set of analyzed cells and dicentric frequencies, ideally within 20% of the actual whole-body dose received by the individual.…”
Section: Discussionsupporting
confidence: 82%
“…Beside the well–understood dependence on time after exposure due to focus loss [17], the curve parameters may also depend on different scoring mechanisms [13], the laboratory [13, 19], the technician who is carrying out the scoring [21], the temperature at exposure [22], shipment [23], as well as the cell type investigated [16, 24]. Furthermore, it has been reported that H2AX focus counts exhibit considerable inter–individual variation [13, 17], which can be partly attributed to covariates like age, smoking, or genetic factors [23]. However, Moquet et al [19] argued, referring to [24], that this variation only makes a “small contribution” towards the estimation of calibration curve parameters and their uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was measurable only with more than 2‐Gy irradiation of the blood samples . However, micronucleus method is less sensitive than chromosome aberration technique . In a previously mentioned study with 47 breast cancer cases using 3‐Gy in vitro irradiation before therapy, patients with more translocations (proved by FISH technique) showed less latency period before late skin effects appeared .…”
Section: Discussionmentioning
confidence: 94%